ANALISIS STRATEGI PROMOSI WISATA PULAU KELAPAN KABUPATEN BANGKA SELATAN - Sulis; Fauzi, Dani; Lestari, Zakia Ayu; Pusparinni, Marissa; Marwani, Iga Safa (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2024)
This study examines the marine tourism potential of Kelapan Island, located in South Bangka Regency, and the promotional strategies needed to increase tourist arrivals. Based on data from Dinas Pariwisata, Kepemudaan, dan Olahraga, South Bangka (2019-2023), it can be seen that domestic tourist arrivals have continued to increase post-COVID-19 pandemic, while foreign tourist arrivals have dropped dramatically. The main obstacles faced are lack of promotion, limited infrastructure, and difficult accessibility. This research aims to formulate an effective promotional strategy to increase public awareness of Kelapan Island's tourism potential. The method used was descriptive qualitative, with data collection through observation and interviews with the Tourism Office, community leaders, and tourists. SWOT analysis was conducted to evaluate the strengths, weaknesses, opportunities, and threats in tourism development. The results showed that Kelapan Island has great tourism potential, especially in marine and culinary tourism. However, inadequate infrastructure and lack of promotion hinder tourism development. Promotion strategies through digital marketing, creative infrastructure development such as eco-glamping, and collaboration with travel agents are proposed as solutions. This study concludes that collaboration between the government, local communities and businesses is essential in the development of sustainable tourism on Kelapan Island. Future research can focus on the implementation of regenerative promotional strategies and their impact on increasing the number of visits, as well as the development of sustainable community-based ecotourism.